ASSESSMENT OF ENVIRONNEMENTAL QUALITY IN SOIL UNDER WHEAT AND VINES IN BOUZNIKA-BENSLIMANE REGION OF MOROCCO - Zaakour Fatna; Chemsi Zakaria; Matech Fatimaezzahra; Moustarhfer Kawtar; Najib Saber (European Scientific Journal, ESJ, 2014)
This work aims at assessing the environmental quality of agricultural soils under vine and wheat cultivation in the area of Bouznika-Benslimane (Morocco). 50 soil samples were collected and studied. The results obtained been studied and recorded on the agronomic parameters, show that the soil’s texture is a little clay with a slightly acid pH neutral. Moreover, the electrical conductivity values are clearly higher in soils under wheat than in those under vine. The variability of CaCO3 contents within the different studied soils is generally similar in all stations. Moreover, the organic substance rate seems to be more important in the soils under the wheat crops (2%) than in those under the vine crops (1, 7%). The examined soil samples under vine and wheat have shown that these soils contain an important concentration of metal trace elements, essentially the Cu (0, 81 ppm), the Cd (0, 85 ppm), the Ni (81, 86 ppm), the Pb (67, 14 ppm) and the Zn (791, 63 ppm). These metallic elements were also detected in significant concentrations within the soils under vine with a pollution index of high (PI).